Effect of competitive adsorption on zinc removal from aqueous solution and zinc smelting effluent by eucalyptus leaf-based magnetic biosorbent. Issue 9 (29th July 2017) - Chen, Cheng; Tang, Yankui; Liu, Yuyang; Liang, Yuanzhang; Zhang, Kaixuan; Wang, Shengye; Liang, Yan
ABSTRACT: The objectives of this study were to investigate the competitive sorption behaviors and mechanisms of heavy metals onto ELMB, a novel eucalyptus-leaf-based magnetic biosorbent, and to study the potential application of ELMB in the treatment of actual zinc smelting effluent after a necessary pretreatment process. ELMB and ELMB-metals systems were characterized using several techniques. Competitive sorption of Zn 2+ with Pb 2+, Cu 2+ and Cd 2+ onto ELMB was studied by batch experiments and the used sorbent was separated under a magnetic field. The results show that the ELMB can be considered as paramagnetic material with various functional groups on its surface. The presence of Pb 2+, Cu 2+ and Cd 2+ significantly decreases the sorption of Zn 2+ in either the binary system or multimetal systems. The order of adsorption preference is Pb 2+ > Cu 2+ > Cd 2+ > Zn 2+ in multimetal systems and the sequence of competitive ability to zinc is: Pb 2+ > Cu 2+ > Cd 2+ . Non-competitive Langmuir multicomponent isotherm model fits to the adsorption data of Pb 2+ and Cu 2+ well in aqueous solution. The co-existent Ca 2+ and SO4 2− decrease the removal efficiencies of heavy metals while the presence of Na + and Cl − shows little effect in the multimetal solution. In the case of actual zinc smelting effluent, "pretreatment + ELMB sorption" is successfully applied to remove heavy metals and the contents of Zn 2+ and its associated metals are well below discharge limits.